Influence of Data Delivery on Availability of Web Systems. (2017) - Walkowiak, Tomasz; Kamiński, Wojciech
Abstract: Meeting the performance expectation of web systems is a challenging task. Data grids, used as an additional tier in n-tier architecture of web applications, allow to speed up access to data. The key process in building of a data grid solution is the initial load, since the default methods of the initial load are very time consuming. Therefore, they have a big influence on lowering system availability. Authors propose a custom adapter that shorts the initial load time and, as a result, enlarges availability of a web system. Authors analysis the default initial load process and comparethe performance of default methods with the adapter developed by them.